No Signs of Genetic Erosion in a 19th Century Genome of the Extinct Paradise Parrot (Psephotellus pulcherrimus) - Martin Irestedt; Per G. P. Ericson; Ulf S. Johansson; Paul Oliver; Leo Joseph; Mozes P. K. Blom (Diversity, 2019)
The Paradise Parrot, Psephotellus pulcherrimus, was a charismatic Australian bird that became extinct around 1928. While many extrinsic factors have been proposed to explain its disappearance, it remains unclear as to what extent genetic erosion might have contributed to the species’ demise. In this study, we use whole-genome resequencing to reconstruct a 15x coverage genome based on a historical museum specimen and shed further light on the evolutionary history that preceded the extinction of the Paradise Parrot. By comparing the genetic diversity of this genome with genomes from extant endangered birds, we show that during the species’ dramatic decline in the second half of the 19th century, the Paradise Parrot was genetically more diverse than individuals from species that are currently classified as endangered. Furthermore, demographic analyses suggest that the population size of the Paradise Parrot changed with temperature fluctuations during the last glacial cycle. We also confirm that the Golden-shouldered Parrot, Psephotellus chrysopterygius, is the closest living relative of this extinct parrot. Overall, our study highlights the importance of museum collections as repositories of biodiversity across time and demonstrates how historical specimens can provide a broader context on the circumstances that lead to species extinctions.